Relationship Status Of Working Mothers With Breastfeeding Eksklucif In Infants Aged 7-12 Months At The Clinic Syahruddin - Atika Pohan; Debby Pratiwi; Paradila Sandi; Paramita Mustari; Sri Junita Simaremare (Sean Institute, 2023)
Exclusive breastfeeding is breastfeeding as early and as much as possible from birth to 6 months without additional fluids or other foods, even water. In other words, exclusive breastfeeding means only breast milk as the only food, without any additives. To determine the relationship between the Status of working mothers with exclusive breastfeeding in infants aged 7-12 months at the clinic syahruddin. This researchi is analytic using Acidental sampling with a population of 40 people the sample of researchers as much as 20 people. Pengelolahan data dengan cara Editing, Coding, Trasfering, Tabulating. MenunjuShows that there is a relationship between maternal age and exclusive breastfeeding in infants aged 7-12 months at the clinic syahruddin P-Value = 0.000. uShows that there is a relationship between working mother education and exclusive breastfeeding in infants aged 7-12 months at the syahruddin clinic P-Value = 0.000. And there is a relationship menunjubetween the type of work of mothers with exclusive breastfeeding in infants aged 7-12 months at the clinic syahruddin P-Value = 0.000. From the results of respondents there is a relationship of age with exclusive breastfeeding in infants aged 7-12 months with a P-value of 0.000. There hubungan is an educational relationship with exclusive breastfeeding in infants aged 7-12 months with a P-value of 0.000. And aDA relationship type of work with exclusive breastfeeding in infants aged 7-12 months with a P-value of 0.000. The results of this study are expected to increase knowledge about working mothers with exclusive breastfeeding in infants aged 7-12 months at the syahruddin clinic. So that working mothers know about the importance of exclusive breastfeeding for babies 7-12 months.